Stem Cell–Driven Cellular Pathways in Craniofacial Bone Remodeling and Dental Tissue Regeneration: An Experimental Study in Dental Clinics of Alexandria, Egypt - Aml Aljayer (AlQalam Journal of Medical and Applied Sciences, 2026)
Stem cell therapy has emerged as a promising approach for craniofacial bone remodeling and dental tissue regeneration. In this study, a mixed-methods design was employed, combining laboratory analyses with clinical data from 100 participants. Results demonstrated that 80% of respondents had received mesenchymal stem cell (MSC) therapy, with 70% reporting improvements in bone density and 65% noting enhanced dental tissue regeneration. Imaging tests confirmed progress in 85% of cases, while overall satisfaction with therapy outcomes was reported by 80–85% of participants. Correlation analysis revealed strong positive relationships between stem cell treatment and improvements in bone and dental tissues, with coefficients ranging from 0.60 to 0.70 (p < 0.01). Side effects were minimal, with only 20% reporting complications such as swelling or pain. These findings underscore the therapeutic potential of stem cell-based interventions, highlighting both their efficacy and safety. The study concludes that stem cell therapy represents a viable and effective strategy for regenerative dentistry and craniofacial surgery, though larger multicenter trials are needed to standardize protocols and validate long-term outcomes.